Ethyl-acetate fraction from a cinnamon-cortex extract protects pancreatic β-cells from oxidative stress damage - Li, Weiling; Qiao, Jialu; Lin, Kuan; Sun, Ping; Wang, Yuansong; Peng, Qian; Ye, Xiansheng; Liu, Wei; Sun, Binlian (Frontiers in Pharmacology, 2023)
The pathogenesis of diabetes mellitus is mediated mainly by oxidative stress produced by damaged pancreatic β-cells. We identified that an ethyl-acetate fraction (EA) from a cinnamon-cortex extract (CCE) is rich in flavonoid, and showed no toxicity to β cells. In this study, we evaluated the pharmacologic activities of EA on pancreatic β cells using a model of oxidative stress induced by H2O2 or alloxan. The results showed that EA could significantly reduce reactive oxygen (ROS) accumulation to improve the survival of cells. Western blot showed that EA treatment upregulated expression of nuclear factor erythroid 2 related factor 2, heme oxygenase-1, and gamma glutamylcysteine synthetase. The same model study found that EA also can protect β cells against the apoptosis of pancreatic β cells induced by oxidative stress. Furthermore, EA can enhance insulin secretion in rat and mouse β cell lines treated or not with alloxan or H2O2. The expression of the insulin transcription factor PDX-1 increased upon EA treatment in an EA concentration-dependent manner. At last, the major functional compounds of EA analysis showed that three compounds, cinnamyl alcohol, coumarin, and cinnamic acid, had similar effects as EA. In sum, our data suggested that EA fraction from CCE can protect β cells from oxidative stress, and increase insulin secretion to improve the function of β cells. This function might be due to these three compounds found in EA. Our findings provide a theoretical basis and functional molecules for the use of CCE against diabetes mellitus.